Efficacy and safety of continuous every‐2‐week dosing of ixekizumab over 52 weeks in patients with moderate‐to‐severe plaque psoriasis in a randomized phase III trial (IXORA‐P). (15th May 2018) - Langley, R.G.; Papp, K.; Gooderham, M.; Zhang, L.; Mallinckrodt, C.; Agada, N.; Blauvelt, A.; Foley, P.; Polzer, P.
Summary: Background: Ixekizumab is an interleukin‐17A antagonist approved for treatment of moderate‐to‐severe plaque psoriasis with a recommended 160‐mg starting dose, then 80 mg every 2 weeks (Q2W) to week 12, and every 4 weeks (Q4W) thereafter. Objective: To evaluate continuous Q2W dosing over 52 weeks. Methods: In this phase III, multicentre, double‐blinded, parallel‐group trial, three ixekizumab dosing regimens were assessed for efficacy and safety at week 52 in patients with moderate‐to‐severe plaque psoriasis randomized at a 2 : 1 : 1 ratio to continuous Q2W ( n = 611), continuous Q4W ( n = 310) or dose adjustment per protocol (Q4W/Q2W, n = 306), each with a 160‐mg starting dose. Dose adjustment was determined by predefined criteria to which investigators were blinded; 72 (23?5%) patients in the Q4W/Q2W group adjusted dose. Efficacy outcomes were evaluated using logistic regression. Results: Co‐primary end points were met at week 52: Psoriasis Area and Severity Index 75 responses for Q2W and Q4W dose groups were 85·9% and 79·0%, respectively ( P = 0·006), and static patient global assessment 0/1 responses for Q2W and Q4W dose groups were 78·6% and 70·6%, respectively ( P = 0·005). Treatment‐emergent and serious adverse events were comparable across dose groups. Conclusions: Ixekizumab Q2W had higher efficacy at week 52 than ixekizumab Q4W, with no increase in safety events. Abstract : What's already known about this topic? Recommended label dosing (160‐mg loading dose at week 0, 80 mg every 2 weeks to week 12, and 80 mg every 4 weeks thereafter) of ixekizumab has been shown in three phase III trials to be highly efficacious with an acceptable safety profile in patients with moderate‐to‐severe psoriasis. Prior studies of ixekizumab did not evaluate efficacy and safety of continuous every‐2‐week dosing beyond 12 weeks in patients with psoriasis. What does this study add? In this phase III trial, patients with moderate‐to‐severe psoriasis treated continuously with every‐2‐week vs. every‐4‐week ixekizumab had higher efficacy, with comparable safety profiles, at 52 weeks. Linked Comment: Borghi. Br J Dermatol 2018; 178 :1237–1238 . Respond to this article